2005
DOI: 10.2151/jmsj.83.69
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal/Regional Variation of Variability Characteristic of Daily Maximum/Minimum Temperatures in Japan Observed and Reproduced by RegCM Nested in NCAR-CSM

Abstract: Observation data and output of a regional climate model, RegCM2.5, nested in a global climate model, NCAR-CSM, were analyzed to determine the standard deviation and frequency of extreme values, which were used as indices to characterize the variability of the daily minimum ðT min Þ and maximum ðT max Þ temperatures in Japan. The frequency of extreme values, which are defined in this paper as deviations greater than twofold the standard deviation, was estimated from data using a new method. The significant resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The higher trend of minimum temperature than maximum temperature indicates a decrease of daily temperature range, as found for many other regions of the world (Karl et al, 1991(Karl et al, , 1993IPCC, 2001), although IPCC (2007) has reported no change in global daily temperature range for 1979-2004. For day-to-day variability, our result for maximum and 850hPa temperature corresponds to global warming simulations for Japan and Korea (Kadokura and Kato, 2005;Boo et al, 2006), where daily temperature variance is predicted to be almost unchanged as CO 2 increases. On the other hand, our analysis has revealed that temperature trends after 1980 are as large as 0.4-0.5℃/decade, which is substantially higher than the global and Northern Hemispheric land averages (0.235 ℃ /decade and 0.287 ℃ /decade, respectively, for 1976-2004: JMA, 2005).…”
Section: Summary and Remarkssupporting
confidence: 62%
See 1 more Smart Citation
“…The higher trend of minimum temperature than maximum temperature indicates a decrease of daily temperature range, as found for many other regions of the world (Karl et al, 1991(Karl et al, , 1993IPCC, 2001), although IPCC (2007) has reported no change in global daily temperature range for 1979-2004. For day-to-day variability, our result for maximum and 850hPa temperature corresponds to global warming simulations for Japan and Korea (Kadokura and Kato, 2005;Boo et al, 2006), where daily temperature variance is predicted to be almost unchanged as CO 2 increases. On the other hand, our analysis has revealed that temperature trends after 1980 are as large as 0.4-0.5℃/decade, which is substantially higher than the global and Northern Hemispheric land averages (0.235 ℃ /decade and 0.287 ℃ /decade, respectively, for 1976-2004: JMA, 2005).…”
Section: Summary and Remarkssupporting
confidence: 62%
“…On the other hand, there can be different changes in variability according to periods (Klein Tank et al, 2003). Some of global warming simulations have predicted changes in temperature variability as a result of increased CO 2 concentration , although the change is found to be small in studies for Japan and Korea (Kadokura and Kato, 2005;Boo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%